Full-Length Transcriptomics Reveals Complex Molecular Mechanism of Salt Tolerance in Bromus inermis L. - Li, Qian; Song, Jiaxing; Zhou, Yi; Chen, Yingxia; Zhang, Lei; Pang, Yongzhen; Zhang, Bo (Frontiers in Plant Science, 2022)
Bromus inermis L. (commonly known as smooth bromegrass) is a grass species with high nutritional value, great palatability, cold tolerance, and grazing resistance, which has been widely cultivated for pasture and sand fixation in northern and northwestern China. Salt stress is a main environmental factor limiting growth and production of smooth bromegrass. In this study, we performed PacBio Iso-Seq to construct the first full-length transcriptome database for smooth bromegrass under 300 mM NaCl treatment at different time points. Third-generation full-length transcriptome sequencing yielded 19.67 G polymerase read bases, which were assembled into 355,836 full-length transcripts with an average length of 2,542 bp. A total of 116,578 differentially expressed genes were obtained by comparing the results of third-generation sequencing and second-generation sequencing. GO and KEGG enrichment analyses revealed that multiple pathways were differently activated in leaves and roots. In particular, a number of genes participating in the molecular network of plant signal perception, signal transduction, transcription regulation, antioxidant defense, and ion regulation were affected by NaCl treatment. In particular, the CBL-CIPK, MAPK, ABA signaling network, and SOS core regulatory pathways of Ca2+ signal transduction were activated to regulate salt stress response. In addition, the expression patterns of 10 salt-responsive genes were validated by quantitative real-time PCR, which were consistent with those detected by RNA-Seq. Our results reveal the molecular regulation of smooth bromegrass in response to salt stress, which are important for further investigation of critical salt responsive genes and molecular breeding of salt-tolerant smooth bromegrass.